Troubles with Joining: Decisions of The Great People’s Assembly held on 25th November 1918 and their Legal (In)effectiveness - Božić, Marko D (Glasnik Advokatske komore Vojvodine, 2024)
This paper is about to discuss legal consequences of the act of unilateral secession made on November 25th 1918 by Great People’s Assemble gathered in Novi Sad, as an event that was well described by historiography, but has not yet been under scrutiny of the legal doctrine. The aim of the paper is twofold. Firstly, it reconsiders the act of Great People’s Assembly from the perspective of International Law of that time and, secondly, reexamines its meaning in the context of provisional constitutional order of the first Yugoslav state. The outcomes of both analyses deny the mainstream narrative of Vojvodina’s joining the Kingdom of Serbia. Namely, the results of the first analyses point out that the sovereignty over the territory of present-day Vojvodina could not have been transferred by a unilateral act of 1918 in favor of Serbia, but only by Trianon peace treaty of 1920 in favor of Yugoslavia. The findings of the second analyses, however, indicate that till 1921 and the voting of the first Yugoslav Constitution, Vojvodina and Serbia were not acting as one and unique political entity, but as two distinct et equal autonomous Yugoslav units instead.